Implementation of Inquiry Method on Students' Critical Thinking Ability in the Concept of Structure and Function of Plant Networks - Andalia, Nurlena; Ridhwan, Muhammad; Roslina, Roslina; Afni, Nur; AG, Burhanuddin (Universitas Malikussaleh, 2019)
This study aims to determine the implementation of inquiry methods that can improve students' critical thinking skills on the concept of structure and function of plant tissues at the Sekolah Keberbakatan Olah Raga Negeri Aceh (Aceh State Sports School). The population of this research is the many 112 students of class XI of the Sekolah Keberbakatan Olah Raga Negeri Aceh. The sample in this study were 26 students in class XI-1 as an experimental class and 26 students in class XI-2 as a control class. The method used is a descriptive method with a structural approach. Data collection is done by test techniques and data processing using the t-test formula. The results of the data analysis showed that the average ability or average value of class XI-1 students of the Sekolah Keberbakatan Olah Raga Negeri Aceh in taking the test received 80.7. While the average value of class XI-2 students of the Sekolah Keberbakatan Olah Raga Negeri Aceh in taking the test gets 70. Based on the price of t-counts and t-tables at a significant level of 0.05 with db: 50 of the sample class XI, then t- the count is 6.40 and the t-table is 1.66. So that the hypothesis proposed the implementation of inquiry methods can improve students' critical thinking skills on the concept of the structure and function of plant tissues in the Sekolah Keberbakatan Olah Raga Negeri Aceh is Accepted. It is recommended that this research can increase knowledge through the use of inquiry methods in all biological science subject matter.